Nine Lies about Work : a Freethinking Leader's Guide to the Real World - Buckingham, Marcus (Gildan, 2019)
Your organization's culture is the key to its success. Strategic planning is essential. People's competencies should be measured and their weaknesses shored up. People crave feedback. These may sound like basic truths of our work lives today. But actually, they're lies.